Positive electrode material, lithium ion battery and preparation method and application thereof

By forming a nickel lithium silicate clad layer on the surface of the matrix material of the high-nickel positive electrode material, and realizing the embedding and construction of lithium under low temperature conditions in the liquid phase, the problem of poor circulation stability of the high-nickel positive electrode material is solved, the structural stability of the positive electrode material and the lithium ion transmission rate are improved, and the cycle stability of the battery is significantly improved.

CN119812261APending Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411962565.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

High-nickel positive electrode materials are prone to rupture during charging and discharging, increasing side reactions with the electrolyte, accelerating aging, and continuously decreasing the electrochemical performance of the positive electrode materials. How to improve the cyclic stability of high-nickel positive electrode materials is the focus of research.

Method used

A lithium-containing transition metal oxide is used as the matrix material, and a nickel-lithium silicone clad layer is formed on its surface. By simultaneously realizing the intercalation of lithium and the construction of the surface clad layer under the liquid phase low temperature conditions, a positive electrode material with high structural stability and excellent electronic conductivity is prepared.

Benefits of technology

The cladding layer of the cathode material is closely combined with the matrix material, has high structural stability, excellent lithium ion transmission rate, and significantly improves the cycle stability and electrochemical properties of the cathode material, so that the battery assembled from the cathode material has excellent cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812261A_ABST
    Figure CN119812261A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a lithium ion battery as well as a preparation method and application of the lithium ion battery. The positive electrode material comprises a base material and a coating layer coating at least part of the surface of the base material, the base material comprises a lithium-containing transition metal oxide, and the material of the coating layer comprises lithium nickel silicate. When the positive electrode material is sintered and prepared, a coating layer and a base material can be combined more tightly, so that the positive electrode material has excellent electronic conductivity and lithium ion transmission rate, lithium in the positive electrode material is favorably embedded and separated, and a battery assembled by the positive electrode material has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode material, a lithium ion battery, and a preparation method and application thereof. Background Art

[0002] Ternary layered oxides such as nickel-cobalt-manganese (NCM) and nickel-cobalt-aluminum (NCA) can significantly improve the specific capacity of cathode materials and the energy density of batteries due to the increase in nickel content. However, layered high-nickel cathode materials are prone to rupture during the charge and discharge process, increase side reactions with the electrolyte, accelerate aging, and continuously reduce the electrochemical performance of the cathode materials. Therefore, how to improve the cycle stability of high-nickel cathode materials is a research focus in this field.

[0003] At present, most of the coating layers are set on the surface of the positive electrode materials to improve the cycle stability of the positive electrode materials. At this stage, the coating layer can be directly formed on the surface of the positive electrode material. For example, the patent document CN110336018B discloses a composite layer of polyaniline and poly 4-vinylpyridine coated on the surface of the nickel cobalt manganese oxide material; the coating precursor layer can also be first formed on the surface of the positive electrode material precursor, and then sintered and crystallized to obtain the coating layer. For example, the patent document CN114203986A discloses coating sodium silicate on the surface of the positive electrode material precursor, and then mixing with lithium salt and sintering to form Li 1.5 Na 0.5 SiO3 coating layer, however, the above coating layer hinders the diffusion of lithium in the process of insertion and extraction to a certain extent, affecting the cycle performance of the positive electrode material. In addition, the above coating layer is not tightly combined with the matrix material and is easy to fall off, which will still lead to a decrease in the electrochemical performance of the positive electrode material in the subsequent electrochemical process.

[0004] Therefore, how to improve the cycle stability of positive electrode materials is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The present invention provides a positive electrode material, wherein the coating layer of the positive electrode material is tightly combined with a base material, has high structural stability, and also has excellent electronic conductivity and lithium ion transmission rate, which is beneficial to the embedding and extraction of lithium in the positive electrode material, so that a battery assembled with the positive electrode material has excellent cycle stability.

[0006] The present invention also provides a method for preparing a positive electrode material, which can simultaneously complete the embedding of lithium and the construction of a surface coating layer under liquid phase low temperature conditions, is conducive to preparing a positive electrode material with excellent performance, and the preparation process is simple and easy to operate.

[0007] The present invention also provides a lithium ion battery. Due to the inclusion of the positive electrode material, the lithium ion battery has excellent cycle stability.

[0008] In a first aspect of the present invention, there is provided a positive electrode material, the positive electrode material comprising a base material and a coating layer coating at least a portion of the surface of the base material;

[0009] The matrix material includes a lithium-containing transition metal oxide, and the coating layer material includes lithium nickel silicate.

[0010] The positive electrode material as described above, wherein the chemical formula of the lithium-containing transition metal oxide is LiNi x Co y Mn z O2, where x+y+z=1, x≥0.6, 0<y≤0.3, 0<z≤0.6;

[0011] The chemical formula of the lithium nickel silicate is LiNiSiO4.

[0012] The positive electrode material as described above, wherein the coating layer has a thickness of not less than 4 nm.

[0013] The positive electrode material as described above, wherein the electronic conductivity of the positive electrode material is 10 -6 ~10 -3 S / m.

[0014] The positive electrode material as described above, wherein the capacity retention rate of the positive electrode material is not less than 92% after being cycled for 300 cycles at 60° C.; the capacity retention rate of the positive electrode material is not less than 95% after being cycled for 100 cycles at 25° C.

[0015] A second aspect of the present invention provides a method for preparing the positive electrode material according to the first aspect, comprising the following steps:

[0016] The transition metal hydroxide is subjected to surface hydroxylation treatment to obtain a transition metal oxyhydroxide;

[0017] Mixing transition metal oxyhydroxide, tetraethyl orthosilicate, and a solvent to obtain a first reaction system;

[0018] Adjusting the pH value of the first reaction system to allow ethyl orthosilicate to undergo a hydrolysis reaction and form SiO2 on the surface of the transition metal oxyhydroxide, thereby obtaining a second reaction system;

[0019] adjusting the pH value of the second reaction system, adding a lithium source and a divalent nickel source to the second reaction system, raising the temperature and reacting to obtain a reaction product;

[0020] The reaction product is sintered in an oxidizing atmosphere to obtain a positive electrode material.

[0021] The preparation method as described above, wherein a transition metal hydroxide, an oxidant and a solvent are mixed to carry out the surface hydroxylation treatment, wherein the oxidant comprises at least one of oxygen, chlorine, sodium dichromate, potassium dichromate, potassium permanganate, potassium persulfate, nitric acid, hydrogen peroxide, peracetic acid, chromic acid, ammonium persulfate, sodium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, potassium perborate, bromine and iodine; the solvent comprises at least one of water, ethanol, propylene glycol, acetone, ethanol, chloroform, ether, acetic acid, acetone, acetonitrile, isopropanol and methanol; and / or,

[0022] The lithium source includes at least one of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium chloride, lithium nitrate and lithium hydroxide; and / or,

[0023] The divalent nickel source includes at least one of nickel oxide, nickel sulfide, nickel chloride, nickel sulfate, nickel acetate, nickel nitrate, nickel carbonate, and nickel hydroxide.

[0024] The preparation method as described above, wherein the pH value of the first reaction system is adjusted to 9-14; and / or,

[0025] Adjusting the pH of the second reaction system to 5-7; and / or,

[0026] The molar ratio of the lithium element in the lithium source to the transition metal element in the transition metal hydroxide is (1-1.15):1; and / or,

[0027] The molar ratio of the tetraethyl orthosilicate to the transition metal hydroxide is (1-10):100; and / or,

[0028] The molar ratio of the nickel element in the divalent nickel source to the transition metal element in the transition metal hydroxide is (1-15):100, and / or,

[0029] The temperature is raised to 50-200° C., and the reaction time is 1-50 hours.

[0030] In the preparation method as described above, the sintering treatment is carried out at a temperature of 600 to 1000° C. and for a time of 1 to 20 hours.

[0031] A third aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the positive electrode material described in the first aspect or the positive electrode material prepared by the preparation method described in the second aspect.

[0032] The implementation of the present invention has at least the following beneficial effects:

[0033] In the positive electrode material provided by the present invention, lithium nickel silicate is a lithium ion conductor with a layered structure, which can effectively provide a diffusion channel for lithium ions and help improve the transmission rate of lithium ions; secondly, the coating layer as a physical barrier layer can protect the base material from direct contact with the electrolyte, thereby slowing down the phase change, dissolution or structural damage of the material, and improving the structural stability and cycle performance of the positive electrode material; at the same time, lithium nickel silicate can react with HF formed by decomposition of the electrolyte, reducing HF corrosion of the positive electrode material, thereby improving the cycle performance of the positive electrode material; in addition, the Si coating layer of the positive electrode material is sintered during the preparation process. 4+ The transition metal ions in the matrix material diffuse under the high temperature of sintering treatment and move relative to each other in the lattice to form a solid solution, so that the coating layer and the matrix material are more tightly combined at the lattice level, further improving the structural stability of the positive electrode material, thereby making the battery assembled with the positive electrode material have excellent cycle stability.

[0034] The method for preparing the positive electrode material provided by the present invention adopts transition metal oxyhydroxide as the coated object, realizes the embedding of lithium and the construction of the surface coating layer simultaneously under liquid phase low temperature conditions, and the preparation process is simple and easy to operate.

[0035] The lithium ion battery provided by the present invention comprises the above-mentioned positive electrode material, so the lithium ion battery also has excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a SEM image of the positive electrode material in Example 1 of the present invention;

[0037] Figure 2 It is a SEM picture of the positive electrode material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In a first aspect of the present invention, a positive electrode material is provided, which includes a base material and a coating layer covering at least a portion of the surface of the base material, wherein the base material includes a lithium-containing transition metal oxide, and the material of the coating layer includes lithium nickel silicate.

[0040] The structure and composition of the positive electrode material will directly affect the structure and performance of the positive electrode material. Among them, the base material is the core of the positive electrode material, and the coating layer covers part or all of the surface of the base material. At this time, the coating layer can be used as a physical barrier layer to protect the base material from direct contact with the electrolyte, thereby slowing down the phase change, dissolution or structural damage of the material, which helps to improve the structural stability and cycle performance of the positive electrode material.

[0041] The matrix material includes lithium-containing transition metal oxides, such as lithium cobalt oxide, lithium iron manganese, ternary materials, lithium cobalt oxide, etc., wherein the ternary materials include lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA).

[0042] The material of the coating layer includes lithium nickel silicate, which has a layered structure and is a lithium ion conductor with high conductivity. Using lithium nickel silicate as the coating layer material can increase the diffusion channel of lithium ions, which helps to improve the lithium ion transmission rate of the positive electrode material. It can be understood that the lithium ion transmission rate and the electronic conductivity are positively correlated. The higher the lithium ion transmission rate, the higher the electronic conductivity; the lower the lithium ion transmission rate, the lower the electronic conductivity. In addition, lithium nickel silicate can react with HF formed by the decomposition of the electrolyte, reduce the corrosion of HF to the positive electrode material, and thus improve the cycle performance of the positive electrode material.

[0043] It should be noted that when the positive electrode material of the present invention is sintered, the Si in the coating layer 4+ The transition metal ions in the matrix material will diffuse under the high temperature of sintering treatment and move relative to each other in the lattice to form a solid solution, making the coating layer and the matrix material more tightly bonded in the lattice structure, which helps to further improve the structural stability of the positive electrode material, thereby making the battery assembled from the positive electrode material have excellent cycle stability.

[0044] In addition, lithium nickel silicate is insoluble in water, so applying the positive electrode material of the present invention to a battery can reduce the requirements for water and humidity control and simplify the manufacturing steps.

[0045] In some embodiments, the chemical formula of the lithium-containing transition metal oxide is LiNi x Co y Mn z O2, where x+y+z=1, x≥0.6, 0<y≤0.3, 0<z≤0.6; the chemical formula of lithium nickel silicate is LiNiSiO4. At this time, both the base material and the coating layer contain nickel elements and have similar lattice structures. The base material and the coating layer match well, which can reduce the stress caused by the interface mismatch between the base material and the coating layer, and make the coating layer and the base material further tightly combined, thereby further improving the structural stability of the positive electrode material.

[0046] In the scheme of the present invention, the coating thickness of the positive electrode material is not less than 4nm, which helps to inhibit the side reaction between the positive electrode material and the electrolyte and improve the long cycle life of the positive electrode material under the premise of improving the electronic conductivity of the positive electrode material. In some embodiments, since the coating thickness is not less than 4nm, the positive electrode material of the present invention is scanned by X-ray photoelectron spectroscopy (XPS), and when the scanning range is 2-4nm on the surface of the positive electrode material, the coating layer of the positive electrode material of the present invention can be semi-quantitatively analyzed.

[0047] The positive electrode material provided by the present invention has excellent electronic conductivity and cycle performance. In some embodiments, the electronic conductivity of the positive electrode material is 10 -6 ~10 -3 In some embodiments, the positive electrode material is cycled for 300 cycles at 60° C., and the capacity retention rate is not less than 92%; the positive electrode material is cycled for 100 cycles at 25° C., and the capacity retention rate is not less than 95%.

[0048] The second aspect of the present invention provides a method for preparing a positive electrode material, comprising the following steps: subjecting a transition metal hydroxide to a surface hydroxylation treatment to obtain a transition metal oxyhydroxyl group; mixing the transition metal oxyhydroxyl group, tetraethyl orthosilicate, and a solvent to obtain a first reaction system; adjusting the pH value of the first reaction system to allow the tetraethyl orthosilicate to undergo a hydrolysis reaction and form SiO2 on the surface of the transition metal oxyhydroxyl group to obtain a second reaction system; adjusting the pH value of the second reaction system, adding a lithium source and a divalent nickel source to the second reaction system, raising the temperature and reacting to obtain a reaction product; and sintering the reaction product in an oxidizing atmosphere to obtain a positive electrode material.

[0049] The transition metal hydroxide may be, for example, Ni x Co y Mn z OH, after surface hydroxylation of transition metal hydroxides, Ni x Co y Mn z OOH; wherein x+y+z=1, x≥0.6, 0<y≤0.3, 0<z≤0.6. The transition metal hydroxide may also be Ni x Co y Al z OH, after surface hydroxylation of transition metal hydroxides, Ni x Co y Al z OOH; wherein, x+y+z=1, x≥0.6, 0<y≤0.3, 0<z≤0.6.

[0050] Specifically, a transition metal hydroxide, an oxidant and a solvent can be mixed to carry out the above-mentioned surface hydroxylation treatment, wherein the oxidant includes at least one of oxygen, chlorine, sodium dichromate, potassium dichromate, potassium permanganate, potassium persulfate, nitric acid, hydrogen peroxide, peracetic acid, chromic acid, ammonium persulfate, sodium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, potassium perborate, bromine and iodine; and the solvent includes at least one of water, ethanol, propylene glycol, acetone, ethanol, chloroform, ether, acetic acid, acetone, acetonitrile, isopropanol and methanol.

[0051] The transition metal oxyhydroxide, tetraethyl orthosilicate and solvent are mixed to obtain a first reaction system. In the first reaction system, the surface of the transition metal oxyhydroxide contains a large number of hydroxyl groups. By adjusting the pH value of the first reaction system, tetraethyl orthosilicate (TEOS) is essentially promoted to undergo hydrolysis and condensation reaction on the surface of the transition metal oxyhydroxide to form a silicon-based skeleton, and SiO2 is formed on the surface of the transition metal oxyhydroxide to obtain a second reaction system. SiO2 can play a bridging role, and it will combine with the transition metal oxyhydroxide to form a silicate group. When the lithium source and divalent nickel source are subsequently introduced, the negatively charged silicate group attracts the positively charged lithium source and divalent nickel source, thereby generating a nickel silicate lithium coating layer and forming a lithium ion amplification channel. Among them, the equation for the reaction of tetraethyl orthosilicate (TEOS) on the surface of the transition metal oxyhydroxide is Si(OCH2CH3)4+2H2O=SiO2+4C2H5OH.

[0052] Among them, tetraethyl orthosilicate is prone to hydrolysis and condensation reaction in an alkaline environment. In some embodiments, the pH value of the first reaction system is adjusted to 9-14, and specifically, ammonia water can be added to the first reaction system to adjust the pH. The pH value of the first reaction system can be adjusted along with temperature increase, specifically, the temperature can be increased to 60-100°C.

[0053] Specifically, the solvent includes at least one of an alcohol solvent and water. For example, ethanol and water may be mixed to form a solvent, and then transition metal hydroxide oxide and tetraethyl orthosilicate are added to the solvent, wherein the volume ratio of alcohol to water is (10:1) to (2:1).

[0054] The pH of the second reaction system is adjusted to promote the reaction of SiO2 with the lithium source and the divalent nickel source to form lithium nickel silicate. In some embodiments, adjusting the pH of the second reaction system to 5 to 7 helps to promote the formation of lithium nickel silicate. Too high a pH value may cause side reactions to generate impurities such as NiO and Li4SiO4.

[0055] By introducing a lithium source and a divalent nickel source into the second reaction system, raising the temperature and reacting, in this reaction stage, a portion of the lithium source is embedded in the matrix material to form the matrix material, and another portion of the lithium source reacts with the divalent nickel source and the surface SiO2 to form a nickel silicate lithium coating layer. In some embodiments, the temperature is raised to 50 to 200°C, and the reaction time is 1 to 50 hours. Under the above-mentioned liquid phase low temperature conditions, the embedding of lithium and the construction of the surface ion conductor coating can be achieved simultaneously, without the need for a sintering step, which helps to improve production efficiency.

[0056] The present invention does not limit the specific types of lithium source and divalent nickel source. For example, in some embodiments, the lithium source includes at least one of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium chloride, lithium nitrate, and lithium hydroxide; and / or, the divalent nickel source includes at least one of nickel oxide, nickel sulfide, nickel chloride, nickel sulfate, nickel acetate, nickel nitrate, nickel carbonate, and nickel hydroxide.

[0057] The present invention does not limit the amount of each raw material added, as long as it is guaranteed to form a positive electrode material precursor that satisfies the above-mentioned structure and components. For example, in some embodiments, the molar ratio of lithium element in the lithium source to the transition metal element in the transition metal hydroxide is (1-1.15):1; and / or, the molar ratio of tetraethyl orthosilicate to the transition metal hydroxide is (1-10):100; and / or, the molar ratio of nickel element in the divalent nickel source to the transition metal element in the transition metal hydroxide is (1-15):100.

[0058] After the temperature is raised and the reaction occurs, the reaction system is filtered, washed and dried. Filtration is used to remove excess liquid, and washing is to remove introduced ionic impurities. After drying, the reaction product can be obtained, which can also be called a positive electrode material precursor.

[0059] The reaction product of the present invention only needs to be sintered once to obtain the positive electrode material. The sintering process is to achieve crystallization and improve the stability of the crystal structure. In some embodiments, the sintering temperature is 600 to 1000°C and the time is 1 to 20 hours. During the sintering process, Si 4+ The process refers to the mutual penetration of silicon ions (Si 4+ ) and the transition metal ions in the matrix material will undergo ion diffusion at high temperature, that is, they move relative to each other in the crystal lattice, thereby forming a solid solution between the coating layer and the matrix material. This process helps to anchor the coating layer, that is, the coating layer and the matrix material are more closely combined, increasing the adhesion of the interface, and making the coating layer and the matrix material more closely combined at the lattice level, thereby improving the structural integrity and cycle stability of the positive electrode material.

[0060] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material provided in the first aspect or the positive electrode material prepared by the preparation method provided in the second aspect.

[0061] The lithium-ion battery of the present invention includes a positive electrode sheet, which can also be prepared by conventional technical means in the art. Specifically, the above-mentioned positive electrode material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry, and then the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode collector. After drying, the positive electrode sheet of the present invention can be obtained.

[0062] The lithium ion battery of the present invention includes a separator, a negative electrode sheet and an electrolyte in addition to a positive electrode sheet. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also adopt separators conventionally used in the art, such as PP film, PE film, etc. The lithium ion battery of the present invention can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained by a stacking or winding process, and then the above lithium ion battery can be obtained by baking, injection, formation, packaging and other processes.

[0063] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0064] Example 1

[0065] The preparation of the positive electrode material in this embodiment includes the following steps:

[0066] 1) Ni was treated with sodium persulfate in deionized water 0.8 Co 0.1 Mn 0.1 OH is oxidized to Ni 0.8 Co 0.1 Mn 0.1 OOH;

[0067] 2) Ni 0.8 Co 0.1 Mn 0.1 OOH and tetraethyl orthosilicate (TEOS) are dispersed in a mixed solution of ethanol and deionized water at a molar ratio of 1:0.05 to obtain a first reaction system; wherein the volume ratio of ethanol to deionized water in the mixed solution is 9:1; then ammonia water is added to the first reaction system to adjust the pH value to 10, and stirred for 6 hours to obtain a second reaction system;

[0068] 3) Adjust the pH of the second reaction system to 6, and add Ni 0.8 Co0.1 Mn 0.1 The OOH molar amount of 1.05 times of LiOH solution and 0.15 times of NiSO4 solution were heated to 90°C and stirred for 12 hours to react to obtain a reaction product;

[0069] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 750° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0070] Example 2

[0071] The preparation of the positive electrode material in this embodiment includes the following steps:

[0072] 1) Use ammonium persulfate solution to 0.6 Co 0.1 Mn 0.3 OH is oxidized to Ni 0.6 Co 0.1 Mn 0.3 OOH;

[0073] 2) Ni 0.6 Co 0.1 Mn 0.3 OOH and TEOS are dispersed in anhydrous ethanol at a molar ratio of 1:0.03 to obtain a first reaction system; then, ammonia water is added to the first reaction system to adjust the pH value to 9, the temperature is raised to 60° C., and stirred for 6 hours to obtain a second reaction system;

[0074] 3) Adjust the pH of the second reaction system to 6, and add Ni 0.6 Co 0.1 Mn 0.3 A LiOH solution with a molar amount of 1.05 times OOH and a NiSO4 solution with a molar amount of 0.1 times OOH were heated to 90°C and stirred for 12 hours to react to obtain a reaction product;

[0075] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 750° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0076] Example 3

[0077] The preparation of the positive electrode material in this embodiment includes the following steps:

[0078] 1) Use potassium persulfate solution to 0.9 Co 0.05 Mn 0.05 OH is oxidized to Ni 0.9 Co 0.05 Mn 0.05 OOH;

[0079] 2) Ni0.9 Co 0.05 Mn 0.05 OOH and TEOS are dispersed in anhydrous ethanol at a molar ratio of 1:0.05 to obtain a first reaction system; then, ammonia water is added to the first reaction system to adjust the pH value to 12, the temperature is raised to 60° C., and stirred for 6 hours to obtain a second reaction system;

[0080] 3) Adjust the pH of the second reaction system to 5, add Ni 0.9 Co 0.05 Mn 0.05 A LiOH solution with a molar amount of 1.05 times that of OOH and a NiSO4 solution with a molar amount of 0.1 times that of OOH were heated to 100°C and stirred for 8 hours to react to obtain a reaction product;

[0081] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 750° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0082] Example 4

[0083] The preparation of the positive electrode material in this embodiment includes the following steps:

[0084] 1) Use potassium persulfate solution to 0.8 Co 0.1 Al 0.1 OH is oxidized to Ni 0.8 Co 0.1 Al 0.1 OOH;

[0085] 2) Ni 0.8 Co 0.1 Al 0.1 OOH and TEOS are dispersed in anhydrous ethanol at a molar ratio of 1:0.05 to obtain a first reaction system; then, ammonia water is added to the first reaction system to adjust the pH value to 14, the temperature is raised to 70° C., and stirred for 6 hours to obtain a second reaction system;

[0086] 3) Adjust the pH of the second reaction system to 7, and add Ni 0.8 Co 0.1 Mn 0.1 A LiNO3 solution with a molar amount of 1.05 times OOH and a Ni(NO3)2 solution with a molar amount of 0.15 times OOH were heated to 100°C and stirred for 8 hours to react to obtain a reaction product;

[0087] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 780° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0088] Example 5

[0089] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 2), ammonia water is added to the first reaction system to adjust the pH value to 8, and the mixture is stirred for 6 hours to obtain a second reaction system.

[0090] Example 6

[0091] The preparation of the positive electrode material in this embodiment can refer to Example 1, the only difference being that in step 3) in this embodiment, the pH of the second reaction system is adjusted to 4.5.

[0092] Example 7

[0093] The preparation of the positive electrode material in this embodiment can refer to that in Embodiment 1, the only difference is that in step 3) in this embodiment, the LiOH solution is replaced by a LiCl solution.

[0094] Example 8

[0095] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 3) in this embodiment, the NiSO4 solution is replaced by a NiO solution.

[0096] Example 9

[0097] The preparation of the positive electrode material in this embodiment can refer to Example 1, the only difference is that in step 3), the NiSO4 solution in this embodiment is replaced by Ni(OH)2 solution.

[0098] Example 10

[0099] The preparation of the positive electrode material in this embodiment can refer to Example 1, the only difference is that in step 2) in this embodiment, Ni 0.8 Co 0.1 Mn 0.1 OOH and tetraethyl orthosilicate (TEOS) are dispersed in propylene glycol at a molar ratio of 1:0.05 to obtain a first reaction system.

[0100] Embodiment 11

[0101] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 4) in this embodiment, the obtained powder is placed in an oxygen atmosphere at 850° C. for 10 h to obtain the positive electrode material.

[0102] Example 12

[0103] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 4) in this embodiment, the obtained powder is placed in an oxygen atmosphere at 950° C. for 6 hours to obtain the positive electrode material.

[0104] Embodiment 13

[0105] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 4) in this embodiment, the obtained powder is placed in an oxygen atmosphere at 1000° C. for 5 h to obtain the positive electrode material.

[0106] Embodiment 14

[0107] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 4) in this embodiment, the obtained powder is placed in an oxygen atmosphere at 820° C. for 10 h to obtain the positive electrode material.

[0108] Embodiment 15

[0109] The preparation of the positive electrode material in this embodiment can refer to that in embodiment 1, the only difference is that in step 4) in this embodiment, the obtained powder is placed in an oxygen atmosphere at 780° C. for 9 hours to obtain the positive electrode material.

[0110] Comparative Example 1

[0111] The preparation of the positive electrode material of this comparative example comprises the following steps:

[0112] 1) Ni 0.8 Co 0.1 Mn 0.1 OH and TEOS were dispersed in anhydrous ethanol at a molar ratio of 1:0.05, ammonia water was added to adjust the pH value to 9, the temperature was raised to 60°C, and stirred for 6 hours to obtain a first reaction product;

[0113] 2) After filtering the first reaction product, drying it at 60° C. to obtain a second reaction product; mixing the second reaction product with LiOH at a molar ratio of 1.03:1 and grinding for 30 minutes to obtain a mixture; treating the mixture at 750° C. for 10 hours in an oxygen atmosphere to obtain a positive electrode material.

[0114] Comparative Example 2

[0115] The preparation of the positive electrode material of this comparative example comprises the following steps:

[0116] 1) Ni 0.8 Co 0.1 Mn 0.1 OH and LiOH were mixed in a molar ratio of 1.05:1 and ground for 30 min to obtain a first mixture; the first mixture was treated at 750 ° C for 10 h in an oxygen atmosphere to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2;

[0117] 2) LiNi 0.8 Co 0.1 Mn 0.1O2 and TEOS were dispersed in anhydrous ethanol at a molar ratio of 1:0.05, ammonia water was added to adjust the pH value to 9, the temperature was raised to 60°C, and stirred for 6 hours to obtain a first reaction product;

[0118] 3) After filtering the first reaction product, drying it at 60° C. to obtain a second reaction product; mixing the second reaction product powder with LiOH at a molar ratio of 1:1.03 and grinding for 30 minutes to obtain a second mixture; treating the second mixture at 750° C. for 10 hours in an oxygen atmosphere to obtain a positive electrode material.

[0119] Comparative Example 3

[0120] The preparation of the positive electrode material of this comparative example comprises the following steps:

[0121] 1) Ni was treated with sodium persulfate in deionized water 0.8 Co 0.1 Mn 0.1 OH is oxidized to Ni 0.8 Co 0.1 Mn 0.1 OOH;

[0122] 2) Ni 0.8 Co 0.1 Mn 0.1 OOH and tetraethyl orthosilicate (TEOS) are dispersed in a mixed solution of ethanol and deionized water at a molar ratio of 1:0.05 to obtain a first reaction system; wherein the volume ratio of ethanol to deionized water in the mixed solution is 9:1; then ammonia water is added to the first reaction system to adjust the pH value to 10, and stirred for 6 hours to obtain a second reaction system;

[0123] 3) Adjust the pH of the second reaction system to 6, and add Ni 0.8 Co 0.1 Mn 0.1 1.1 times the molar amount of OOH in LiOH solution and 0.12 times the molar amount of Na2SO4 solution, heated to 90°C and stirred for 12h to react to obtain a reaction product;

[0124] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 750° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0125] Comparative Example 4

[0126] The preparation of the positive electrode material of this comparative example comprises the following steps:

[0127] 1) Ni was treated with sodium persulfate in deionized water 0.8 Co 0.1 Mn 0.1 OH is oxidized to Ni 0.8Co 0.1 Mn 0.1 OOH;

[0128] 2) Ni 0.8 Co 0.1 Mn 0.1 OOH and tetraethyl orthosilicate (TEOS) are dispersed in a mixed solution of ethanol and deionized water at a molar ratio of 1:0.05 to obtain a first reaction system; wherein the volume ratio of ethanol to deionized water in the mixed solution is 9:1; then ammonia water is added to the first reaction system to adjust the pH value to 10, and stirred for 6 hours to obtain a second reaction system;

[0129] 3) Adjust the pH of the second reaction system to 7, and add Ni 0.8 Co 0.1 Mn 0.1 LiOH solution with 1.05 times the molar amount of OOH;

[0130] 4) After filtering the reaction product, it was dried at 60° C., and the obtained powder was treated at 750° C. for 10 h in an oxygen atmosphere to obtain a positive electrode material.

[0131] Comparative Example 5

[0132] The preparation of the positive electrode material of this comparative example comprises the following steps:

[0133] 1) Ni was treated with sodium persulfate in deionized water 0.8 Co 0.1 Mn 0.1 OH is oxidized to Ni 0.8 Co 0.1 Mn 0.1 OOH;

[0134] 2) Ni 0.8 Co 0.1 Mn 0.1 OOH and tetraethyl orthosilicate (TEOS) are dispersed in a mixed solution of ethanol and deionized water at a molar ratio of 1:0.05 to obtain a first reaction system; wherein the volume ratio of ethanol to deionized water in the mixed solution is 9:1; then ammonia water is added to the first reaction system to adjust the pH value to 10, and stirred for 6 hours to obtain a second reaction system;

[0135] 3) Without adjusting the pH of the second reaction system to 7, a molar amount of Ni 0.8 Co 0.1 Mn 0.1 LiOH solution with 1.03 times the molar amount of OOH (pH reaches 11 at this time);

[0136] 4) After filtering the reaction product, it was dried at 60°C, and the obtained powder was treated at 750°C for 10 hours in an oxygen atmosphere to obtain a positive electrode material containing NiO and Li4SiO4 impurities.

[0137] Test example

[0138] X-ray photoelectron spectroscopy (XPS) analysis test: K-Alpha XPS equipment is used as a test instrument, and an appropriate amount of the positive electrode material prepared in Examples 1-4 of the present invention is taken as a sample and placed on the test platform. By testing the specific spectral line intensities of different atoms, the ratio of Li / Ni / Si / O can be obtained. The results can be seen in Table 1. The specific principle is as follows: After X-ray irradiation, the intensity of photoelectrons emitted from the sample surface (I, referring to the peak area of ​​the characteristic peak) has a linear relationship with the concentration of the atom in the sample (n), which can be simply expressed as: I = n*S, S is called the sensitivity factor. For two elements i and j in a solid sample, if their sensitivity factors Si and Sj are known, and their respective specific spectral line intensities Ii and Ij are measured, then the ratio of their atomic concentrations is ni:nj = (Ii / Si): (Ij / Sj).

[0139] Coating layer thickness test: The positive electrode materials obtained in the embodiments of the present invention and the comparative examples were taken as samples for TEM testing. An obvious interface could be observed on the particle surface of the positive electrode material with the coating layer. The thickness of the coating layer was then analyzed from the TEM photos, and the analysis was performed from 10 different cross-sectional positions. The average value was taken as the thickness of the coating layer.

[0140] Electronic conductivity test: Use a resistivity tester (Suzhou Jingge Electronics ST-2255A), take 5g of the positive electrode material obtained in the embodiment of the present invention and the comparative example as a sample, use an electronic press to press to 5000kg±2kg, and maintain for 15-25s. Place the sample between the electrodes of the tester, sample height h (cm), voltage at both ends U (V), current I (A), area after powder pressing S = 3.14cm 2 The electronic conductivity of each sample was calculated according to the formula σ=h / (S×R) / 1000.

[0141] Cyclic stability (300 cycle retention rate) test: After the positive electrode materials prepared in the embodiments of the present invention and the comparative examples are prepared into positive electrode sheets, the metal lithium sheet is used as the counter electrode, the diaphragm is used to separate the positive and negative electrodes, and 30 microliters of ternary commercial electrolyte (the electrolyte is LiPF6, and the solvent is EC-DEC-EMC with a volume ratio of 1:1:1) is added. The button battery is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, positive electrode, and positive electrode shell, and finally packaged with a sealing machine.

[0142] The steps of preparing the positive electrode sheet include: dissolving the positive electrode material: conductive agent acetylene black: binder polyethylene = 96.5%: 1.5%: 2% in a certain amount of solvent 2-methylpyrrolidone (NMP) according to the mass ratio, mixing to a slurry with moderate viscosity, and then evenly coating the slurry on the aluminum foil. The coated electrode sheet is placed in a vacuum oven at 120°C and dried for 2 hours. After it is completely dried, use a punching machine to cut it into circular electrode sheets with a diameter of 10 mm. After recording its mass, put it in a vacuum oven at 120°C and dry it for 12 hours to remove moisture, and finally store it in a glove box under an argon atmosphere. The surface loading of the prepared positive electrode sheet is 15 mg / cm 2 about.

[0143] The cycle performance of the lithium-ion battery was tested at 25°C at 3-4.3V with 0.5C charge / 1C discharge for 100 cycles and 300 cycles, and the capacity retention rate after 300 cycles was calculated according to the following formula.

[0144] 100-cycle capacity retention rate = 100th-cycle discharge capacity / first-cycle discharge capacity*100%;

[0145] 300-cycle capacity retention rate = 300th-cycle discharge capacity / first-cycle discharge capacity*100%.

[0146] The test results are shown in Table 2.

[0147] Table 1

[0148]

[0149] Table 2

[0150]

[0151] Figure 1 is a SEM image of the positive electrode material of Example 1. Figure 1 It can be seen that the positive electrode material in Example 1 is a secondary sphere formed by agglomeration of primary particles, and has a good crystal form; Figure 2 This is the SEM image of the positive electrode material of Comparative Example 1. Figure 2 It can be seen that the positive electrode material in Comparative Example 1 is a single crystal agglomerated particle of primary particle aggregation, which is the effect caused by lithium silicate as a coating layer during the sintering stage.

[0152] According to Table 1, the positive electrode materials prepared in Examples 1-15 have a Li mass percentage of 4.29%-4.81% within the range of 2-4nm on the surface under XPS scanning, a Ni mass percentage of 37.17%-37.76%, a Si mass percentage of 17.14%-18.21%, and a Si mass percentage of 40.19%-41.18%. It can be seen that the coating layer of the positive electrode material of the present invention is lithium nickel silicate, and the chemical formula is LiNiSiO4.

[0153] According to Table 2, the positive electrode material provided by the present invention has excellent cycle stability. The inventor believes that the positive electrode material provided by the present invention can make the coating layer and the base material more closely combined during sintering preparation, which helps to promote the positive electrode material to have excellent electronic conductivity and lithium ion transfer rate, and is conducive to the insertion and extraction of lithium in the positive electrode material, so that the battery assembled by the positive electrode material has excellent cycle stability. Comparative Example 1 uses conventional methods to make lithium silicate as a coating layer, and the performance of the obtained positive electrode material is poor; Comparative Example 2 needs to be sintered twice, resulting in a decrease in the performance of the positive electrode material, and the preparation process is complicated; the coating layer of the positive electrode material in Comparative Example 3 is Li 1.5 Na 0.5 SiO3 is easy to fall off, which is not conducive to improving the performance of the positive electrode material; in Comparative Example 4, the coating layer of the positive electrode material is Li2SiO3, and Comparative Example 5 does not adjust the pH of the second reaction system, resulting in an excessively high pH value, generating impurities such as NiO and Li4SiO4.

[0154] The preferred specific embodiments and experimental verification of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a base material and a coating layer coating at least a portion of the surface of the base material; The matrix material includes a lithium-containing transition metal oxide, and the coating layer material includes lithium nickel silicate.

2. The positive electrode material according to claim 1, characterized in that The chemical formula of the lithium-containing transition metal oxide is LiNi x Co y Mn z O2, where x+y+z=1, x≥0.6, 0<y≤0.3, 0<z≤0.6; The chemical formula of the lithium nickel silicate is LiNiSiO4.

3. The positive electrode material according to claim 1 or 2, characterized in that The coating layer has a thickness of not less than 4 nm.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The electronic conductivity of the positive electrode material is 10 -6 ~10 -3 S / m.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material has a capacity retention rate of not less than 92% after being circulated for 300 cycles at 60° C.; and a capacity retention rate of not less than 95% after being circulated for 100 cycles at 25° C.

6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The transition metal hydroxide is subjected to surface hydroxylation treatment to obtain a transition metal oxyhydroxide; Mixing transition metal oxyhydroxide, tetraethyl orthosilicate, and a solvent to obtain a first reaction system; Adjusting the pH value of the first reaction system to allow ethyl orthosilicate to undergo a hydrolysis reaction and form SiO2 on the surface of the transition metal oxyhydroxide, thereby obtaining a second reaction system; adjusting the pH value of the second reaction system, adding a lithium source and a divalent nickel source to the second reaction system, raising the temperature and reacting to obtain a reaction product; The reaction product is sintered in an oxidizing atmosphere to obtain a positive electrode material.

7. The preparation method according to claim 6, characterized in that: The surface hydroxylation treatment is performed by mixing a transition metal hydroxide, an oxidant and a solvent, wherein the oxidant comprises at least one of oxygen, chlorine, sodium dichromate, potassium dichromate, potassium permanganate, potassium persulfate, nitric acid, hydrogen peroxide, peracetic acid, chromic acid, ammonium persulfate, sodium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate, potassium perborate, bromine and iodine; the solvent comprises at least one of water, ethanol, propylene glycol, acetone, ethanol, chloroform, ether, acetic acid, acetone, acetonitrile, isopropanol and methanol; and / or, The lithium source includes at least one of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium chloride, lithium nitrate and lithium hydroxide; and / or, The divalent nickel source includes at least one of nickel oxide, nickel sulfide, nickel chloride, nickel sulfate, nickel acetate, nickel nitrate, nickel carbonate, and nickel hydroxide.

8. The preparation method according to claim 6 or 7, characterized in that: Adjusting the pH value of the first reaction system to 9-14; and / or, Adjusting the pH of the second reaction system to 5-7; and / or, The molar ratio of the lithium element in the lithium source to the transition metal element in the transition metal hydroxide is (1-1.15):1; and / or, The molar ratio of the tetraethyl orthosilicate to the transition metal hydroxide is (1-10):100; and / or, The molar ratio of the nickel element in the divalent nickel source to the transition metal element in the transition metal hydroxide is (1-15):100, and / or, The temperature is raised to 50-200° C., and the reaction time is 1-50 hours.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The sintering process is carried out at a temperature of 600 to 1000° C. and for a time of 1 to 20 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • A modified lithium nickel cobalt manganese oxide material, its preparation method and application

    CN110336018B

  • Method for improving electrochemical performance of LiNi0. 8Co0. 15Al0. 05O2 positive electrode material

    CN114203986A